Conceptual framework for systemic capacity strengthening for health policy and systems research. Issue 8 (3rd August 2022) - Mirzoev, Tolib; Topp, Stephanie M; Afifi, Rima A; Fadlallah, Racha; Obi, Felix Abrahams; Gilson, Lucy
Abstract : Health policy and systems research (HPSR) is critical in developing health systems to better meet the health needs of their populations. The highly contextualised nature of health systems point to the value of local knowledge and the need for context-embedded HPSR. Despite such need, relatively few individuals, groups or organisations carry out HPSR, particularly in low-income and middle-income countries. Greater effort is required to strengthen capacity for, and build the field of, HPSR by capturing the multilevel and nuanced representation of HPSR across contexts. No comprehensive frameworks were found that inform systemic HPSR capacity strengthening. Existing literature on capacity strengthening for health research and development tends to focus on individual-level capacity with less attention to collective, organisational and network levels. This paper proposes a comprehensive framework for systemic capacity strengthening for HPSR, uniquely drawing attention to the blurred boundaries and amplification potential for synergistic capacity strengthening efforts across the individual, organisational and network levels. Further, it identifies guiding values and principles that consciously acknowledge and manage the power dynamics inherent to capacity strengthening work. The framework was developed drawing on available literature and was peer-reviewed by the Board and Thematic Working Groups of Health Systems Global. While the framework focuses on HPSR, it may provide a useful heuristic for systemic approaches to capacity strengthening more generally; facilitate its mainstreaming within organisations and networks and help maintain a focused approach to, and structure repositories of resources on, capacity strengthening.